Synthesis and Reactions of 2-Carboxyvinyl-4-chloro-6,8-dibromoquinazoline and Some New Fused Triazolo-quinazoline Derivatives - El-Badry, Y.A. (Asian Journal of Chemistry, 2010)
Synthesis of the 2-carboxyvinyl-4-chloro-6,8-dibromoquinazoline (2) has been established based on chlorination of the corresponding 6,8-dibromoquinazoline analogue. The simple replacement of the chlorine atom at 4-position of quinazoline nucleus with different amines has produced compounds of the type 4-heteroaryl-quinazoline derivatives and the fused [2-carboxyvinyl-6,8- dibromo quinazoline]-[quinazolin-4-one]. The reaction of the titled chloro-quinazoline derivative (2) with hydrazine hydrate and subsequent condensation with different aromatic aldehydes is furnished a series of fused 5-substituted-1,2,4-triazolo-quinazoline derivatives. Finally, its reaction with acyl hydrazide mainly, acetyl hydrazide is furnished the non-mixed heterocyclic system called 5-methyl-1,2,4-triazolo[4,3-c](6,8-dibromo-2-carboxyvinyl)quinazoline.